Novel silk fibroin/elastin wound dressings - Vasconcelos, Andreia (2012)
Silk fibroin (SF) and elastin (EL) scaffolds were successfully produced for the first time for the treatment of burn wounds. The self-assembly properties of SF, together with the excellent chemical and mechanical stability and biocompatibility, were combined with elastin protein to produce scaffolds with the ability to mimic the extracellular matrix (ECM). Porous scaffolds were obtained by lyophilization and were further crosslinked with genipin (GE). Genipin crosslinking induces the conformational transition from random coil to β-sheet of SF chains, yielding scaffolds with smaller pore size and reduced swelling ratios, degradation and release rates. All results indicated that the composition of the scaffolds had a significant effect on their physical properties, and that can easily be tuned to obtain scaffolds suitable for biological applications. Wound healing was assessed through the use of human full-thickness skin equivalents (EpidermFT). Standardized burn wounds were induced by a cautery and the best re-epithelialization and the fastest wound closure was obtained in wounds treated with 50SF scaffolds; these contain the highest amount of elastin after 6 days of healing in comparison with other dressings and controls. The cytocompatibility demonstrated with human skin fibroblasts together with the healing improvement make these SF/EL scaffolds suitable for wound dressing applications.